Sustainable well-being subjective indicators: Human interdependence with other humans and with the environment - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (Springer, 2018)
The intention of this study is to assess the theories and current approaches to well-being and sustainability to help identify the dimensions and influencing factors for sustainable well-being for Malaysia. Problem: Studies on the subjective measure of sustainable well-being exhibit high attention to human interdependence with other humans (HIH) and human interdependence with the environment (HIE). However, a conclusive study concerning the dimensions and influencing factors that determine the interdependencies is lacking. Approach: An exploratory review was adopted to identify the dimensions and influencing factors of HIH and HIE. Findings: The study discovered that both HIH and HIE have four dimensions each. The dimensions for HIH are (i) personal empowerment, (ii) positive relations, (iii) organisational opportunity and (iv) community development. The dimensions for HIE are (v) individual personality, (vi) interaction with nature, (vii) environmental attitude and (viii) external conditions. Limitation: The full reliance on literatures is the weakness of the paper. An empirical study is needed to prove the applicability of the dimensions and influencing factors discovered. Significance: The key findings of HIH and HIE are practical for research exploration in Eastern Muslim and developing countries, such as Malaysia.